Pd-mediated intramolecular ketalization of alkynediols: construction of the central [3.2.1]-bicyclic ketal core of cyclodidemniserinol trisulfate - Ramana, C. V.; Mallik, Rosy; Sahoo, Gokarneswar (Tetrahedron Letters, 2009)
A preliminary study dealing with the Pd-mediated alkynediol cycloisomerization to construct the central bicyclic ketal core of cyclodidemniserinol trisulfate is documented. (c) 2009 Elsevier Ltd. All rights reserved.
Keywords: Alkynol cycloisomerization; Bridged bicyclic ketal; Cyclodidemniserinol trisulfate; Yamaguchi oxirane-alkyne coupling